2017
DOI: 10.1177/2192568217732988
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for New Vertebral Fracture After Percutaneous Vertebroplasty

Abstract: Study Design:Retrospective analysis. Level of evidence III.Objectives:Low-energy vertebral compression fractures are an increasing socioeconomic problem among elderly patients. Percutaneous vertebroplasty has been extensively used for the treatment of painful fractures because of its effectiveness. However, some complications have been described; among them, new vertebral compression fractures, whether adjacent or not to the treated vertebra, are commonly reported complications (8% to 52%).Methods:We retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…osteoporosis medication [7,11,15,24]. The technical factors associated with recollapse include a larger or smaller volume of injected cement and performing percutaneous balloon kyphoplasty instead of PVP [7,10]. Statistically significant radiographic risk factors have also been identified, including higher local kyphosis, intravertebral instability, and presence of the IVC sign with pseudarthrosis [6,7,10,13].…”
Section: A B C D a B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…osteoporosis medication [7,11,15,24]. The technical factors associated with recollapse include a larger or smaller volume of injected cement and performing percutaneous balloon kyphoplasty instead of PVP [7,10]. Statistically significant radiographic risk factors have also been identified, including higher local kyphosis, intravertebral instability, and presence of the IVC sign with pseudarthrosis [6,7,10,13].…”
Section: A B C D a B Cmentioning
confidence: 99%
“…Nevertheless, the recollapse of cemented vertebrae or cement loosening seldom occurs and is accompanied by the recurrence of back pain following cement augmentation [6][7][8][9]. Previous studies have identified the risk factors for the recollapse of the vertebra, namely, low bone mineral density (BMD), older age, intradiscal cement leakage, presence of multiple preexisting vertebral fractures, intravertebral vacuum cleft (IVC) sign, and fracture at the thoracolumbar junction [6,7,[10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Venous PMMA embolization is rare, although there have been reports of pulmonary embolism 22,23. Potential negative mechanical effects of cemented vertebrae upon adjacent osteoporotic levels has been described by previous studies,912 with reports of new VCF incidence being extremely variable (8%–52%). Nevertheless the debate on whether PV causes an increased risk of adjacent VCFs is still open.…”
Section: Evidence In the Literaturementioning
confidence: 69%
“…At present, it is uncertain whether PKP / PVP increases the risk of vertebral fractures, especially adjacent vertebral bodies [29]. It has been reported in previous literature that the strength of the vertebral body and the physiological invagination of endplate are aggravated by injecting bone cement into injured vertebrae, which increases the pressure of the intervertebral disc, transfers the load to adjacent vertebrae, and increases the risk of fracture of the adjacent vertebral body [30][31][32]. In this study, the incidence of adjacent vertebral fractures in the surgical treatment group was 7.89%, which was not signi cantly different from that in the conservative treatment group (6.25%) (P > 0.05).…”
Section: Incidence Of Adjacent Vertebral Fracturesmentioning
confidence: 99%